2021
DOI: 10.3390/life11111257
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza Protects Endothelial Dysfunction against Mitochondrial Oxidative Stress

Abstract: Salvia miltiorrhiza (SM) is a common traditional Chinese medicine used in the treatment of cardiovascular and cerebrovascular diseases. Endothelial dysfunction plays an important role in the pathology of cardiovascular diseases. Endothelial dysfunction may induce inflammation and change vascular tone and permeability. The main pathological mechanism of endothelial dysfunction is the formation of reactive oxygen species (ROS). Mitochondria are the main source of energy and can also produce large amounts of ROS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Zingiberis Rhizoma (Gan-Jiang) shows anti-fatigue effects by exciting the adrenal cortex system 41 and regulates the abundances and interactions in the gut microbiota 42 . Salviae Miltiorrhizae Radix et Rhizoma (Dan-Shen) protects endothelial dysfunction against mitochondrial oxidative stress, and exhibits cardiovascular and cerebrovascular protective actions 43 . Acori Tatarinowii Rhizoma (Shi-Chang-Pu) exerts regulatory effects on the neurotransmitter levels, antioxidant stress responses, oxygen free radical scavenging, downregulation of inflammatory mediators, inhibition of neuronal apoptosis, and modulation of neuroglial cells and blood-brain barrier permeability 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Zingiberis Rhizoma (Gan-Jiang) shows anti-fatigue effects by exciting the adrenal cortex system 41 and regulates the abundances and interactions in the gut microbiota 42 . Salviae Miltiorrhizae Radix et Rhizoma (Dan-Shen) protects endothelial dysfunction against mitochondrial oxidative stress, and exhibits cardiovascular and cerebrovascular protective actions 43 . Acori Tatarinowii Rhizoma (Shi-Chang-Pu) exerts regulatory effects on the neurotransmitter levels, antioxidant stress responses, oxygen free radical scavenging, downregulation of inflammatory mediators, inhibition of neuronal apoptosis, and modulation of neuroglial cells and blood-brain barrier permeability 44 .…”
Section: Discussionmentioning
confidence: 99%
“…When combined with A mongholicus Bunge, S miltiorrhiza Bunge can activate the PI3K/ AKT signaling pathway and inhibit the TLR4/nuclear factor κB signaling pathway, resulting in significant anti-inflammatory and antioxidant effects. [29,30] In this study, we identified 46 chemical constituents from the BATMAN-TCM database, including compounds such as neotanshinone C, tanshiquinone B, miltionone I, neocryptotanshinone II, and dihydrokaranone. It has been observed that the main chemical components can interact with other active compounds on multiple targets within the network.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various components extracted from S. miltiorrhiza , DHT is a fat-soluble compound that exhibits anti-inflammatory effects. It is well established that DHT shows strong anti-oxidative and anti-inflammatory properties in inflammation and various other diseases 28 , 36 . In the current study, in vitro experiments demonstrated that DHT mitigates IL-1β-induced damage to human primary chondrocytes.…”
Section: Discussionmentioning
confidence: 99%